Penentangan rakyat Terengganu terhadap Inggeris dan kerajaan pada tahun 1928m mengikut perspektif Islam - Abu Bakar, Abdullah; Basri, Ibrahim (2013)
tries to highlight the fight of the people of Torongganu against the Bath l Col= i u I nn ent during the reign of Sultan Suleiman Badrul Nam Syah. Actually :11m fighlix titt (etel retaliation is the. people as staled by the Britishotho govommonl wMI tow= ham Mu ; ;maul this fight is the jihad of the people to set free the stale of To ;Oat This study is carried out with reference to historical facts, documonls and lastoty Ixxi ;Sin accordance withsyariah law from the stated in the Holy QumtLHod1111 and l'uoalm This research also stresses that the fight is lawful as stated in Syation Low and 111050 my 75 act is better known as the warriors in the fight for independence and those sacrificed Ilml 501 should be remembered and highly appreciated. Keyords: colonial; rebel and retaliation; jihad; fight for independence;syadah law